THE RELATIONSHIP BETWEEN FAST FOOD CONSUMPTION AND PHYSICAL ACTIVITY WITH PRIMARY DYSMENORRHEA IN ADOLESCENTS - Wahyuni, Wahyuni (UI Scholars Hub, 2025)
Background: Menstruation is a bleeding event that occurs when the inner lining of the uterus, known as the endometrium, sheds. Dysmenorrhea is one of the symptoms that teenage girls often feel during menstruation. Dysmenorrhea can affect women's comfort and quality of life. There are two types of dysmenorrhoea, namely primary dysmenorrhea and secondary dysmenorrhoea. Primary dysmenorrhoea refers to the condition of menstrual pain that adolescent girls often experience, with a prevalence rate of 60-90%. Risk factors for primary dysmenorrhoea are influenced by several factors, including fast food intake, physical activity level, stress level, age at first menstruation (menarche), and nutritional status. The purpose is to determine whether there is a correlation between fast food consumption and physical activity and the intensity of primary dysmenorrhoea in adolescents. The method used was a quantitative research type that adopted an observational research design with a cross-sectional study approach, and the sampling technique applied was purposive sampling. A sample of 75 people who met the criteria was obtained. The Results: The results of the research have been tested by SPSS using the Spearman Rank test. The significance value for fast food and primary dysmenorrhea is 0.028, while for the relationship between physical activity and primary dysmenorrhea, the significance value is 0.020. The conclusion: Based on the research results, there is a relationship between fast food consumption. Fast food and physical activity with the intensity of dysmenorrhoea in teenagers at SMA Al-Islam 1 Surakarta.